Estudio de factibilidad para el montaje de una máquina llenadora selladora y codificadora de empaques que mejore la productividad en la industria de cosméticos (2018)
Companies must to think about constantly innovation in their processes, the quality, and the way to generate greater satisfaction of their customers. For this reason, is essential to improve every production processes, and make it competitive. The purpose of this paper is to carry out a feasibility study for the implementation of a new fully automated machinery, in the packaging, sealing and coding processes of the company ESKO LTDA, in order to optimize times, raw materials and costs of human resource, thus generating greater competitiveness against the market in the cosmetics industry.